The Oncoprotein BCL11A Binds to Orphan Nuclear Receptor TLX and Potentiates its Transrepressive Function - Estruch, Sara B.; Buzón, Víctor; Carbó, Laia R.; Schorova, Lenka; Lüders, Jens; Estébanez-Perpiñá, Eva (PLOS ONE, 2012)
Nuclear orphan receptor TLX (NR2E1) functions primarily as a transcriptional repressor and its pivotal role in brain development, glioblastoma, mental retardation and retinopathologies make it an attractive drug target. TLX is expressed in the neural stem cells (NSCs) of the subventricular zone and the hippocampus subgranular zone, regions with persistent neurogenesis in the adult brain, and functions as an essential regulator of NSCs maintenance and self-renewal. Little is known about the TLX social network of interactors and only few TLX coregulators are described. To identify and characterize novel TLX-binders and possible coregulators, we performed yeast-two-hybrid (Y2H) screens of a human adult brain cDNA library using different TLX constructs as baits. Our screens identified multiple clones of Atrophin-1 (ATN1), a previously described TLX interactor. In addition, we identified an interaction with the oncoprotein and zinc finger transcription factor BCL11A (CTIP1/Evi9), a key player in the hematopoietic system and in major blood-related malignancies. This interaction was validated by expression and coimmunoprecipitation in human cells. BCL11A potentiated the transrepressive function of TLX in an in vitro reporter gene assay. Our work suggests that BCL11A is a novel TLX coregulator that might be involved in TLX-dependent gene regulation in the brain.